Submitted for Your Consideration: Potential Advantages of a Novel Clinical Trial Design and Initial Patient Reaction - Loop, Matthew S.; Frazier-Wood, Alexis C.; Thomas, Amy S.; Dhurandhar, Emily J.; Shikany, James M.; Gadbury, Gary L.; Allison, David B. (Frontiers in Genetics, 2012)
In many circumstances, individuals do not respond identically to the same treatment. This phenomenon, which is called treatment response heterogeneity (TRH), appears to be present in treatments for many conditions, including obesity. Estimating the total amount of TRH, predicting an individual’s response, and identifying the mediators of TRH are of interest to biomedical researchers. Clinical investigators and physicians commonly postulate that some of these mediators could be genetic. Current designs can estimate TRH as a function of specific, measurable observed factors; however, they cannot estimate the total amount of TRH, nor provide reliable estimates of individual persons’ responses. We propose a new repeated randomizations design (RRD), which can be conceived as a generalization of the Balaam design, that would allow estimates of that variability and facilitate estimation of the total amount of TRH, prediction of an individual’s response, and identification of the mediators of TRH. In a pilot study, we asked 118 subjects entering a weight loss trial for their opinion of the RRD, and they stated a preference for the RRD over the conventional 2-arm parallel groups design. Research is needed as to how the RRD will work in practice and its relative statistical properties, and we invite dialogue about it.